Effects of captivity and rewilding on amphibian skin microbiomes. (July 2022) - Kueneman, Jordan G.; Bletz, Molly C.; Becker, Matthew; Gratwicke, Brian; Garcés, Orlando A.; Hertz, Andreas; Holden, Whitney M.; Ibáñez, Roberto; Loudon, Andrew; McKenzie, Valerie; Parfrey, Laura; Sheafor, Brandon; et al.
Abstract: Captive breeding to safeguard against extirpation in the wild is a practice for many animal groups. Animals in captivity experience reduced contact with natural substrates and other animals, and consume atypical diets that may alter naturally occurring microbial associations. Amphibian skin microbiomes are vital for amphibian health, protecting them from pathogens and aiding in development, immune system training, and fecundity. Thus, understanding how changes associated with captivity influence microbial communities and the health of captive-reared amphibians is an important consideration in captive breeding and reintroduction programs. Overarching patterns of amphibian microbial diversity in captivity have not been previously explored. Therefore, we conducted a meta-analysis of skin microbes from captive-managed and wild individuals of 18 salamander and frog species from temperate and tropical biomes. We found that microbial composition of captive and wild amphibians differed for all species. However, while the overall captivity effect on amphibian skin richness was significant, the direction of the captivity effect on diversity metrics and antifungal function differed depending on the host species. One species exhibiting a large skin microbiome shift in captivity is the variable harlequin frog, Atelopus varius . A soft-release of A. varius to outdoor mesocosms "restored" the microbiome through time, and frogs also increased antifungal function of their skin microbiome with time in mesocosms. Rewilding the microbiome may influence resistance to diseases such as chytridiomycosis. Indeed, evaluating the outcome of individual species is necessary until we have a cohesive approach to mediate shifts of amphibian skin microbes that result from captivity.